Studi Analisis Perbandingan Pwm Carrier Untuk Multilevel Inverter Tiga Fasa Lima Belas Level Dengan Sumber Input Simetris Terpisah - Effendi; M. Agil Haikal (Jurnal JEETech, 2022)
Inverters are used to convert direct current or DC (Direct Current) sources into alternating current sources or AC (Alternating Current). A method is needed to make the output waveform close to a sinusoidal waveform. The Multi Level Inverter (MLI) method has a large number of levels and is closer to a sinusoidal wave. The three-phase MLI design with a separate symmetrical input source in this study is able to produce a three-phase output wave, where the resulting Total Harmonic Distortion (THD) value is smaller, namely 5.65% when using the Modified PWM method where the carrier signal has no frequency